Rationing Health Care and the Role of the ‘Acute Principle’ - Rivera-López, Eduardo; Justus Liebig University Giessen (My University, 2009)
In several works, Hartmut Kliemt has developed an original account on the necessity of rationing health care and on how a rationing policy should be carried out. While I agree on several important points of that view, there is one important aspect of his account that I do not find plausible: his claim that the so-called `acute principle' (a principle that gives absolute preeminence to rescuing identified lives from dying) should be one of the basic criteria to carry out a rationing policy in a liberal state. After explaining Kliemt's view on rationing health care and, more specifically, the foundations of the acute principle, I argue that the acute principle is not supported by our basic moral intuitions. I then apply the previous argument to the case of rationing, arguing for the necessity of a compromise among intuitions supporting the acute principle and other moral intuitions. Finally, I try to show that a feasible system of public health care services is conceivable. In doing so, I make use, with some relevant modifications, of Kliemt's own ideas.
Keywords: ddc:100; ddc:330